2018
DOI: 10.3747/co.25.4287
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Benefit of Nivolumab in A Canadian Non-Small-Cell Lung Cancer Cohort

Abstract: Background Nivolumab was the first immuno-oncology agent available for the treatment of lung cancer in Canada. In the present study, we evaluated the real-world benefit of nivolumab in Canadian patients with lung cancer.Methods Patients included in the cohort were identified from a registry of patients treated through expanded access to nivolumab before and after Health Canada approval. Demographics were collected from the application forms. Outcome data for the duration of treatment and survival were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 17 publications
8
60
0
Order By: Relevance
“…Historically, patients with ECOG PS > 1 treated with chemotherapy had poor outcomes, with median OS of 1.8e3.6 months [28e30], one-year survival rates of <20% [31], tumour response rates of 16e22% [32], and a high incidence of grade 3e5 TRAEs (44%) [33]. The results presented herein and the findings from previous studies of nivolumab and other antiePD-1 agents [7,24,34,35] suggest that patients with ECOG PS 2 may derive benefit from immunotherapy, with median survival of 4.0e6.8 months [7,24], one-year survival rates of 27% (current study), objective response rates of 11e30% [34e36], and lower incidences of grade 3e4 TRAEs (7% in the current study and 8e12% in previous studies) [24,35]. However, there are concerns over immunotherapy due to the lack of clinical data supporting a favourable benefiterisk profile in this heterogenous population with multiple factors that may contribute to poor performance [37]; randomised studies are warranted to assess clinical benefit in these patients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Historically, patients with ECOG PS > 1 treated with chemotherapy had poor outcomes, with median OS of 1.8e3.6 months [28e30], one-year survival rates of <20% [31], tumour response rates of 16e22% [32], and a high incidence of grade 3e5 TRAEs (44%) [33]. The results presented herein and the findings from previous studies of nivolumab and other antiePD-1 agents [7,24,34,35] suggest that patients with ECOG PS 2 may derive benefit from immunotherapy, with median survival of 4.0e6.8 months [7,24], one-year survival rates of 27% (current study), objective response rates of 11e30% [34e36], and lower incidences of grade 3e4 TRAEs (7% in the current study and 8e12% in previous studies) [24,35]. However, there are concerns over immunotherapy due to the lack of clinical data supporting a favourable benefiterisk profile in this heterogenous population with multiple factors that may contribute to poor performance [37]; randomised studies are warranted to assess clinical benefit in these patients.…”
Section: Discussionmentioning
confidence: 68%
“…However, these pivotal trials provided limited data on patients with squamous NSCLC and poor prognostic factors. More recently, real-world studies have shown that nivolumab is effective and well tolerated in elderly patients and those with poor performance status [7,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…15 However, despite the overall favorable tolerability of nivolumab, 3,4,16 shorter OS has also been observed in patients with poor performance status receiving nivolumab for previously treated advanced NSCLC, including in a European postapproval open-label phase 2 study (CheckMate 171) in patients with squamous tumor histology, 17 in the community-based phase 3b/4 study CheckMate 153, 18 and in other real-world studies. [19][20][21][22] Shorter OS in nivolumab-treated patients with poor ECOG PS is potentially related to suppressed immune function, which would limit the efficacy of nivolumab in activating anticancer immune responses by blocking PD-1Àmediated immune resistance mechanisms. 23 Thus, there is a need for more definitive biomarkers to identify patients with poor performance status who are likely to respond to PD-1 inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, it is licensed for the treatment of locally advanced or metastatic non-small cell lung cancer (NSCLC) after prior chemotherapy. Two large randomised studies in patients with advanced non-squamous (NSq) NSCLC (CheckMate057 [3]) and squamous (Sq) NSCLC (CheckMate017 [4]) comparing nivolumab to docetaxel have demonstrated its efficacy at extending overall survival (OS) [5,6], and the interest of nivolumab in treating NSCLC has been confirmed in many subsequent studies in routine clinical practice [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%